Linking the "recovery and resilience plan" and smart specialisation: The Spanish case - A. Fernández-Zubieta (European Commission, Joint Research Centre (JRC), 2022)
This study aims to analyse the alignment of investments in the Spanish 'Recovery and Resilience Plan' with the Smart Specialisation Strategies priorities (2021- 2027) of the country and its regions to identify opportunities for potential synergies and complementary between funding instruments. The structure and methodology follows Marques Santos (2021) approach that has been applied in the Portuguese case study. This methodology uses the information available in the Plan and its annexes and establishes the steps for carrying out a detailed analysis to identify and to classify the investments and actions able to enhance Research and Development and Innovation (R&I) and regional innovation ecosystems. The analysis indicates that up to exteuro20.5 Billion of the Spanish Plan (29% of available funding for 2021-2023) could potentially support directly and indirectly the Smart Specialisation processes in Spain. Similarly to the Portuguese case, the effect of the identified contributions will greatly depend on the final beneficiaries, project selected, absorption capacity, and governance model.
Keywords: E32; O31; G38; 330; Covid-19 crisis; Innovation; Government Policy; Spain